ACCIDENTS AND INCIDENTS AT BRAZILIAN DAMS: ANALYSIS OF DATA AVAILABLE IN DAM SAFETY REPORTS AND CURRENT LEGISLATION - Amaro da Silva, Romário Stéffano (2021)
In Brazil, the development of the dam engineering can be directly correlated to social and economic progress. Although fundamental, a dam construction and operation invariably involve some level of risk, which must be managed through different mechanisms and tools governed by appropriate laws. This paper aims to scrutinize the data contained in National Water Agency (ANA) reports, published annually following institution of the National Dam Safety Policy (PNSB), pertinent to dams accidents and incidents. This information was cataloged and analyzed in order to identify trends associated to types of accidents and incidents, dam component materials and entrepreneurs involved, as well as the disparities between data available from the different regions of Brazil. There is a lack of basic data in numerous reports, hindering more in-depth statistical analyses. The recurrence of this deficit was observed as well as the need to improve the methodologies used to apply the PNSB guidelines.